Serverless ETL and analytics with AWS Glue : your first one-stop reference guide on AWS Glue and its features /: your first one-stop reference guide on AWS Glue and its features. (2022) - Pathak, Vishal; Vajiraya, Subramanya; Sekiyama, Noritaka; Tanaka, Tomohiro; Quiroga, Albert; Gaur, Ishan
No abstract available